Predictive accuracy of Boussinesq approximation in opposed mixed convection with a high-temperature heat source inside a building. (15th October 2018) - Zhou, Yu; Wang, Mengying; Wang, Manning; Wang, Yi
Abstract: The density model of Boussinesq approximation has been extensively used in mixed convection. Literature have investigated the validity of Boussinesq approximation in natural convection; however, there is no related study in mixed convection. This work aims to investigate the accuracy of Boussinesq approximation in mixed convection. In this paper, mixed convection is generated by a thermal plume from a heat source (natural convection) and a downward air jet from the inlet (forced convection). An experiment is set up to validate the computational fluid dynamics (CFD) simulations for the Boussinesq approximation and incompressible ideal gas density models. Results indicate incompressible ideal gas model can be used as a comparative reference to quantitatively investigate the predictive accuracy of the Boussinesq approximation in simulations. Then, simulation results show the accuracy of Boussinesq approximation in mixed convection correlates with Archimedes number, not temperature difference. Accuracy trends are different for forced convection dominated flow, comparable mixed convection, and natural convection dominated flow. This work is of fundamental importance for the application of Boussinesq approximation in mixed convection with a high-temperature heat source, especially in industrial buildings. Graphical abstract: Highlights: Studied accuracy of Boussinesq approximation in mixed convection. A mixed convection experiment with a high-temperature heat source was set up. Simulation results from two density models were compared. Accuracy of Boussinesq approximation in mixed convection is related with Ar instead of Δ T.